The effects of CDKN2A rs3731249, rs11515, and rs3088440 polymorphisms on cancer risk - Dong, Y.; Wang, X.; Yang, Y-W.; Liu, Y-J. (Cellular and Molecular Biology, 2017)
Many studies have been carried out to examine whether there is an association between CDKN2A polymorphisms and cancer risk, but the results from these studies were controversial. In the present study, we performed a meta-analysis to clarify whether there is an association of CDKN2A polymorphisms and cancer risk. Published reports were searched in PubMed and Google Scholar. ORs with 95% CIs were calculated in the dominant models. Twenty six case-control studies that met the inclusion criteria were included in the final meta-analysis. Overall, we found that rs3731249, rs11515, and rs3088440 polymorphisms were not associated with cancer risk (OR=1.27, 95%CI: 0.79-2.03; OR=0.91, 95%CI: 0.79-1.03; OR=1.02, 95%CI: 0.95-1.09). However, CDKN2A rs3731249 polymorphism was significantly associated with ovarian cancer risk (OR=0.78, 95%CI: 0.65-0.95). A significant association was observed in Asian with rs11515 polymorphism (OR=0.48, 95%CI: 0.28-0.83). This meta-analysis shows that CDKN2A rs3731249 polymorphism was significantly associated with ovarian cancer risk. In addition, CDKN2A rs11515 polymorphism might associate with cancer risk in Asians.